Innovative Gamification in the Digital Age: Improving Reading Comprehension Elementary School Students - Sri Wulan Anggraeni; Depi Prihamdani; Yayan Alpian; Anggy Giri Prawiyogi; Peni Indriyani Putri (Universitas Pendidikan Ganesha, 2026)
In the digital era, elementary school students continue to face challenges in reading comprehension due to low learning motivation and the predominance of conventional instructional approaches that provide limited opportunities for interactive learning. These conditions highlight the need for innovative instructional strategies capable of enhancing students' engagement in reading activities. This study aims to analyze the effectiveness of gamification in improving elementary school students' reading comprehension skills. A quantitative approach employing a One-Group Pretest–Posttest experimental design was adopted, involving 38 fifth-grade students as the research participants. Data were collected using a validated and reliable multiple-choice reading comprehension test and analyzed through descriptive and inferential statistics, including the paired-samples t-test using SPSS. The findings revealed that the implementation of gamification significantly improved students' reading comprehension skills. The integration of game elements, such as points, levels, and challenges, enhanced students' engagement, motivation, and active participation, making the reading process more meaningful and enjoyable. The study concludes that gamification is an effective instructional strategy for improving elementary school students' reading comprehension skills. The findings imply that gamification can serve as a technology-enhanced learning approach to strengthen reading literacy, foster learning motivation, and create more interactive, student-centered learning experiences in elementary education.